THE EFFECT OF WORK STRESS AND WORK CONFLICT ON THE PERFORMANCE OF EMPLOYEES OF THE KARO DISTRICT DISASTER MANAGEMENT AGENCY - Herikson Tampubolon; Benny Purba (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This research was conducted at the Karo District Disaster Management Agency Office located at Jalan Letjend Djamin Ginting No. 62 Kabanjahe. This study aims to determine the influence of occupational stress (X1) and work conflict (X2) on employee performance (Y) at the karo district disaster management agency office, both simultaneously and partially. In this study, the sampling technique used is Non Probability Sampling, namely Saturated Sampling. The number of samples in this study was 63 employees of the Karo District Disaster Management Agency. The type of research used is quantitative descriptive research using a causal associative approach. Hypothesis testing in this study using F test technique and t test with SPSS version 22 application. The results showed that work stress negatively and significantly affected employee performance by -2,426. Work conflicts negatively and significantly affected employee performance by -3,054. Simultaneously work stress and work conflict had a positive and significant effect on the performance of employees of the Karo District Disaster Management Agency office of 11,738. Good management of work stress and work conflicts is needed to improve employee performance.